UNDERSTANDING SOFTWARE DEVELOPER ADAPTATION TO QUANTUM COMPUTING ARCHITECTURAL CONCEPTS - Sameena Tabbsum; Syed Zaffar Iqbal; Palwasha Khalid (Spectrum of Engineering Sciences, 2025)
The rapid advancement of quantum computing presents significant challenges and opportunities for software developers accustomed to classical computing architectures. This study aims to explore how software developers understand, interpret and adapt to the emerging architectural concepts of quantum computing, focusing on their learning processes, conceptual transitions and professional adaptation strategies. A qualitative research design was employed, utilizing semi-structured interviews with twelve software developers from diverse professional backgrounds. Thematic analysis was conducted to identify patterns and themes related to developers' perceptions, challenges, and adaptation pathways concerning quantum computing concepts. Findings reveal a spectrum of adaptation experiences, highlighting three dominant themes: cognitive shift from deterministic to probabilistic thinking, perceived barriers including steep learning curves and lack of practical tools and motivational factors driven by industry relevance and future career prospects. Developers emphasized the critical role of targeted educational resources, community support and incremental exposure to quantum concepts in facilitating adaptation. The study concludes that software developers experience a transformative yet challenging journey when adapting to quantum computing architectures. Tailored learning frameworks, practical experimentation opportunities and industry-academia collaborations can enhance the adaptive capacity of developers, enabling a smoother transition to quantum paradigms.